(untitled) (English Language and Literature (JELL), 2026)
This research investigates Minangkabaunese language dialectal variations of North Lantau Buo and Lareh Sago Halaban sub-dialect, in the level of phonological and lexical. This research uses descriptive-qualitative method to analyse 277 data from 207 Swadesh list and 70 personal data from basic vocabularies used in daily conversation in the two sub-dialects. It is found that there are 102 lexicons in phonological variations with 7 phonological variations identified in North Lintau Buo and Lareh Sago Halaban sub-dialect. They are the insertion of phoneme /h/ at the end of Lareh Sago Halaban’s words; the deletion of phoneme /u/ at the end of Lareh Sago Halaban’s words; phoneme /o/ in North Lintau Buo sub-dialect is replaced with phoneme /a/ in Lareh Sago Halaban sub-dialect; phoneme /ɣ/ is replaced with phoneme /r/; phoneme /u/ is replaced with phoneme /a/; phoneme /t/ is replaced with phoneme /n/; and phoneme /g/ is replaced with phoneme /c /. In addition, there were also 29 lexical variations among those sub-dialects. Lastly, based on the calculation of dialectometrical formula, it is found that the percentage of the differences is 47,3%. This percentage implies that both of sub-dialects are sub-dialectal difference. Overall, the results reveal that the two sub-dialects are characterized by unique linguistic features, which become evident through the variations found between them.